Exploring the key target molecules of angiogenesis in diabetic cardiomyopathy based on bioinformatics analysis - Hu, Fengli; Guo, Ruixue; Zhi, Yaxin; Hu, Haijuan; Tang, Ting; Wang, Pengfei; Xue, Ling (Frontiers in Endocrinology, 2025)
BackgroundsDiabetic cardiomyopathy has a very high incidence and serious clinical consequences, making it an urgent clinical problem to be solved. Angiogenesis is a significant phenotype in the occurrence and development of diabetic cardiomyopathy, especially the damage to angiogenesis of cardiac microvessels, which is inextricably linked to the cardiac risk of diabetic patients. In the current basic and clinical research, there is still a lack of treatment methods that directly target the angiogenesis of diabetic cardiomyopathy. This study hopes to discover the key molecules related to diabetic cardiomyopathy and angiogenesis damage, to provide ideas for possible interventions.MethodsSequencing data of animals and cells were obtained from the GEO database, and differentially expressed genes were analyzed. Subsequently, the angiogenesis-related genes were clustered for functional and pathway analysis. Then, the microangiogenesis of the diabetic mice and the angiogenesis changes of high glucose-stimulated HUVECs were verified, and the top three genes related to diabetic cardiomyopathy and angiogenesis were verified using western blot.Results24 differentially expressed genes associated with angiogenesis were found in GSE241565(human) and GSE215979(mice). Among them, 11 genes showed the same trend in the two databases. Then CD31 staining of diabetic mice hearts showed that microvascular angiogenesis was impaired, high glucose-stimulated HUVECs decreased tube formation, and wound healing migration was weakened. Finally, the top 3 genes most associated with diabetic cardiomyopathy were verified, and there was no significant difference between the changes of Edn1 and Lepr. At the same time, Efnb2 was significantly increased under high glucose stimulation.ConclusionCombined with the sequencing data of animal and cell models of diabetic cardiomyopathy, the differential genes associated with angiogenesis were screened. These findings not only elucidate a novel molecular axis linking angiogenesis damage to diabetic cardiomyopathy but also highlight Efnb2 as a potential therapeutic target.